Gluten-free diet reduces autoimmune diabetes mellitus in mice across multiple generations in a microbiota-independent manner. Issue 127 (February 2022) - Hansen, Camilla H.F.; Larsen, Christian S.; Zachariassen, Line F.; Mentzel, Caroline M.J.; Laigaard, Ann; Krych, Lukasz; Nielsen, Dennis S.; Gobbi, Alex; Haupt-Jorgensen, Martin; Buschard, Karsten; Hansen, Axel K.
Abstract: Experimental and clinical data suggest that a gluten-free diet attenuates the development of type 1 diabetes. A gluten-free diet changes the gut microbiota composition, and such microbial changes are expected to reduce the autoimmune responses. However, in experiments with laboratory mice, a gluten-free diet changes the gut microbiota differently under varying experimental settings, questioning the specific role of the gut microbes. Here we show that a maternal gluten-free diet until weaning of their pups, delayed type 1 diabetes in both dams (parent generation) and offspring (F1 generation) of untreated non-obese diabetic (NOD) mice and in mice treated with a full cocktail of antibiotics that eradicates most of the existing microbiota. Breeding a second (F2) generation of NOD mice, never exposed to the gluten-free diet or the associated microbial changes, also demonstrated a preventative effect on type 1 diabetes even though their parents (the F1 generation) had only been on a gluten-free diet very early in life. Collectively, the experimental data, thus, points towards microbiota-independent dietary protection. Furthermore, both the perinatal gluten-free diet and antibiotic treatment reduced inflammation in the salivary glands and improved glucose challenged beta cell function in the F1 offspring. However, in contrast to the autoimmune response in the pancreas, those changes appeared to be microbiota dependent, as they were missing in the antibiotic treated mice, and do, therefore, not seem to be related to the preventative effect on type 1 diabetes. Interestingly, adoptive transfer of splenocytes from gluten-free fed mice protected NOD.SCID mice from developing diabetes, demonstrating that the anti-diabetic effect of a gluten-free diet was based on early life changes in the evolving immune system. In particular, genes involved in regulation of lymphocyte activation, proliferation, and cell adhesion were highly expressed in the spleen in gluten-free fed mice at weaning compared to control fed mice of the F1 generation, which suggested that gluten promotes autoimmunity by inhibiting immune regulation, though the involvement of the specific genes needs further investigation. In conclusion, gluten-free diet reduces autoimmune inflammation in salivary glands and pancreas in NOD mice in a microbiota-dependent and –independent manner respectively, and has preventative effect on type 1 diabetes by modulating the systemic immune system. Highlights: Gluten-free diet early in life has long-term preventative effect on autoimmunity in both salivary glands and pancreas. Gluten-free diet exerts the anti-diabetic effect in a microbiota-independent manner that remains across multiple generations. Gluten initiates autoimmune responses by modulating systemic immune regulation.